Pesticide Labeling: Miscellaneous Label Parts - Frederick M. Fishel (EDIS)
This document describes some of the smaller, yet important pieces found on the pesticide label. Examples of these various components are provided and their meanings explained.  This document is PI-109, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.